Varieties of Capitalism: A Critique - Fast, Travis (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2016)
The Varieties of Capitalism (VoC) has become the dominant approach in comparative political economy and enjoys wide application and attention in disciplines outside of political science and sociology. Indeed the VoC approach has enjoyed much attention in comparative industrial/employment relations (IR). This article undertakes a critical evaluation of the importation of the VoC paradigm into comparative IR. Inter alia, it is argued that the VoC approach, as it is presently configured, may have little to teach IR scholars because its basic theoretical concepts and methodological priors militate against accounting for change.This article begins with a summary of the routine problems researchers in comparative political economy and comparative IR have encountered when attempting to account for change within the constraints of the VoC paradigm. Here the focus is on the limitations imposed when privileging the national scale and the problems engendered by a heavy reliance on comparative statics methodology infused with the concepts of equilibrium and exogenous shocks. The article then goes beyond these routinely recognized limitations and argues that the importation of terminology from neoclassical economic theory, of which the original VoC statement makes foundational reference, further serves to constrain and add confusion to the comparative enterprise; namely, comparative advantage, Oliver Williamson’s neoclassical theory of the firm, the use of the distinction made between (im)perfect market competition in neoclassical economics and the fuzzy distinction made between firms, markets and networks.In the concluding section we argue that the VoC’s narrow focus on the firm and its coordination problems serve to legitimate IRs traditional narrow focus on labour management relations and the pride of place that HRM now enjoys in the remaining IR departments. Ultimately, however, the embrace of the VoC paradigm by comparative IR is a net negative normative move.